Doped MgAl2O4 semiconductor host nanopowders for tunable primary color emissions for application as white LEDs. (4th November 2021) - Ain, Qurat Ul; Ismail, Bushra; Khan, Asad Muhammad; Khan, Rafaqat Ali; Shah, Faheem; Rehman, Hafiz-Ur; Shahid, Farkhanda
Abstract: The emission of white light from hosts having a single phase and the compromised applicability of a very inert, chemically stable, and structurally diverse MgAl2 O4 led to a quest for improving the structural, optical, thermal and electrical properties for more innovative applications. A slight modification in lattice site occupation can lead to antisite defects which alter the physical properties of the materials. The presence of larger alkaline earth Sr 2+ cations at the T-sites have been found to improve the behavior of the activator Mn 2+ cations which are substituted for Mg 2+ at T-sites. In the current study, a series of Mn 2+ doped derivatives having a general formula of Mg1− x −0.3 Mn x Sr0.3 Al2 O4 ( x = 0.1–0.5) were synthesized using the chemical co-precipitation method. Due to the larger radius of Sr 2+ cations, the lattice strain was observed in the cubic crystal structure of magnesium aluminate spinel (MAS). A decrease in the bandgaps of the doped samples indicates the formation of defect states within the bandgap of MAS. Apart from the bandgap transitions, the capture of electrons at oxygen vacancies is also observed in the UV/Vis spectra. The strong tetrahedral site preference of Mn 2+ is altered by the presence of Sr 2+, hence, some octahedral site occupation of Mn 2+ in the lattice is achieved. The antisite defects along with the occupation of both T- and O-sites by Mn 2+ resulted in novel emission bands centered at 464 nm (blue), 515 nm (green), and 621 nm (red) at λ ex of 380 nm. The emission of the primary colors in a simple lattice with cost-effective and in-toxic constituents can be a possible alternative to the costly rare-earth ions doped complex materials in use to-date.